Psychological comorbidities and functional neurological disorders in women with idiopathic urinary retention: International Consultation on Incontinence Research Society (ICI-RS) 2019 - TARCAN, TUFAN (WILEY, 2020)
Aims Chronic urinary retention occurring in young women is poorly understood and a cause may not be found in a majority of cases. Different psychological comorbidities and functional neurological symptom disorders (FNDs) have been reported; however, these have been poorly explored. Methods At the International Consultation on Incontinence Research Society meeting in 2019, a panel of clinicians generated a proposal to explore the relationship between psychological comorbidities, FNDs, and urinary retention in women with chronic idiopathic urinary retention. Results Psychological comorbidities such as depression and anxiety, and FNDs such as leg weakness and loss of consciousness, have been reported in women with idiopathic urinary retention. Individuals react differently to physical and emotional stressors, and experimental models have demonstrated a relationship between the stress response and developing urinary retention. Trauma, particularly sexual trauma, may be a shared risk factor for developing psychological comorbidities and urinary retention. Children with voiding postponement often suffer from psychological comorbidities and behavioral disturbances; however, there is no evidence to suggest that this progresses to urinary retention in adulthood. Psychogenic urinary retention has been described in the urology and psychiatry literature in the past, and anecdotal cases of successful voiding following psychotherapy have been reported, though the true pathophysiology of this entity is uncertain. Conclusion Psychological and functional disorder comorbidities are reported in women with chronic urinary retention. The nature of the association between urinary retention and functional neurological disorder comorbidities needs to be further explored in terms of a disorder of bladder-brain interaction.
Keywords: anxiety; Fowler's syndrome; functional neurological symptom disorders; psychological disorders; somatization; urinary retention; SACRAL NERVE-STIMULATION; IRRITABLE-BOWEL-SYNDROME; QUALITY-OF-LIFE; SOCIAL STRESS; BLADDER DYSFUNCTION; VOIDING DYSFUNCTION; OVERACTIVE BLADDER; FOWLERS-SYNDROME; TRACT SYMPTOMS; POTENTIAL ROLE